1988
DOI: 10.1172/jci113460
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of cholesterol-rich remnant lipoproteins by human monocyte-derived macrophages is mediated by low density lipoprotein receptors.

Abstract: The uptake and degradation of cholesterol-rich remnant lipoproteins, referred to as are shown in the present study to be mediated by LDL receptors (apoB,E(LDL) Immunoblots of monocyte-macrophage extracts with these antibodies revealed a single protein in human macrophages with an apparent molecular weight identical to that of the apoB,E(LDL) receptor found on human fibroblasts. Like receptors on cultured human fibroblasts, the apoB,E(LDL) receptors on monocyte-macrophages responsible for '25I-j-VLDL and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
75
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 37 publications
4
75
0
1
Order By: Relevance
“…0-VLDL from cholesterol-fed animals has been considered to be the only naturally occurring lipoprotein with the capacity to induce foam cell formation in vitro by interacting with a specific receptor, originally thought to be a distinct /3-VLDL receptor. 25 - 27 Recent evidence shows that uptake and degradation of 0-VLDL by mouse J774, P388D, and peritoneal macrophages 28 - 29 and by human monocyte-derived macrophages 30 is probably mediated by the LDL receptor and not by a unique /3-VLDL receptor. Interest in the interactions of human VLDL with macrophages has been stimulated by the possibility that triglyceride-rich lipoproteins and their remnants may be atherogenic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…0-VLDL from cholesterol-fed animals has been considered to be the only naturally occurring lipoprotein with the capacity to induce foam cell formation in vitro by interacting with a specific receptor, originally thought to be a distinct /3-VLDL receptor. 25 - 27 Recent evidence shows that uptake and degradation of 0-VLDL by mouse J774, P388D, and peritoneal macrophages 28 - 29 and by human monocyte-derived macrophages 30 is probably mediated by the LDL receptor and not by a unique /3-VLDL receptor. Interest in the interactions of human VLDL with macrophages has been stimulated by the possibility that triglyceride-rich lipoproteins and their remnants may be atherogenic.…”
mentioning
confidence: 99%
“…Although not conclusive, these findings suggest that both types of lipoproteins share the same uptake mechanism. Ellsworth et al, 28 using J774 cells, and Koo et al, 29 -30 using mouse peritoneal and human monocyte-derived macrophages, demonstrated that /3-VLDL (from cholesterol-fed animals) are taken up by the LDL receptor.…”
mentioning
confidence: 99%
“…Macrophage LDLr metabolizes LDL and VLDL/chylomicron remnants (1,15,32,33), and uptake of LDL by macrophages through the LDLr can induce foam cell formation in culture (32,34). Thus, previous studies have shown that WT mice that received BM cells with WT LDLr develop larger diet-induced plaques compared with the WT mice that received cells lacking LDLr (18,34).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, because of its low affinity for the LDL receptor on mouse macrophages, LDL does not compete effectively with 125 I-/3-VLDL or apo E-containing lipoproteins for receptor binding. 36 Because the LDL receptor could be fully downregulated after the uptake of ox-LDL by the scavenger receptor, the importance of the uptake of ox-LDL by the LDL receptor is not clear. It was reported recently 37 -38 that on SDS-PAGE, Western blot analysis, and enzyme-linked immunosorbent assay, ox-LDL revealed a positive interaction with Mab MB47 (which was shown to bind to the LDL receptor-binding domains).…”
Section: Discussionmentioning
confidence: 99%
“…LDL binds to MPMs with a 10-fold lower affinity than it does to cultured human fibroblasts. 36 Koo et al 36 reported recently that the LDL receptor on MPMs differs from the same receptors on HMDMs and fibroblasts with regard to its molecular size, binding affinity to LDL, and relative insensitivity to downregulation. Using specific antibodies against the rat liver LDL receptor, Ellsworth et al 39 have shown that MPMs, J774 macrophages, and a mouse fibroblast cell line (3T3) all possess LDL receptors with a molecular weight about 5,000 d less than that of the rat liver LDL receptor.…”
Section: Discussionmentioning
confidence: 99%